Metadados para preservação digital na organização arquivística - Leonardo Mendes Padilha (2010)
The usage and creation of documents in digital contexts is a reality. The majority of data produced and stored around the world is recorded in a digital support. The preservation of digital documents is a challenge, especially within the archival studies scope, in which documents have probative character and historical value. Indeed, this is a relevant question facing the respectable field of Archival Studies. We here approach principles of archival and digital preservation, present considerations about the importance of metadata in the context of digital preservation, and argue about the interdisciplinary bias of the study bounding the Archival Studies presence. We use ontological principles to propose a preliminary information organization stage, named terminological stage in the field of ontologies studies, in which are gathered terms that represent digital metadata. Such set of terms is organized under an international disseminated ontological model.